SCREENING AND IDENTIFICATION OF ANTI-MYCOBACTERIAL PLANTS: Life Science-Biochemistry - NIVEDITA PRIYADARSHINI; ARANGANATHAN V (International Journal of Life Science and Pharma Research, 2019)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis (MTb) and is one of the majorcauses of death in the world. One third of the population suffers with TB and there is no potential drug introduced in the past 5 decades. The drugs currently used are ineffective due to the emergence of MDR (Multidrug Resistant Strain), XDR (Extreme Drug Resistant strain) and other co-infections. Hence there is a need for a potent molecule that can inhibit the growth of mycobacterium effectively. The plant kingdom provides a large variety of naturally occurring phytochemicals and other secondary metabolites which are known to be antibacterial. Therefore the present study focuses on screening and identification of potent antimycobacterial plants. Various parts of the plant including leaves are traditionally used for treating a wide spectrum of diseases. In the screening studies of dry leaf (methanolic extracts) of plants from the Western Ghats region gave rise to two potent anti-mycobacterial plants. These plants were identified as TithoniadiversifoliaHemsl. A. Gray(TD) and CouroupitaguianensisAubl.(CG). Both TD and CG plants showed significant anti-mycobacterial activity conducted by well diffusion assay having clearance zone of 15.6 mm and 17.3 mm respectively. These plant extracts were further purified with polar solvents and potential antimycobacterial extracts were tested for their minimum inhibitory concentrations (MICs). The MICs for TD ethyl acetate extract and CG chloroform extract were reported as less than 64µg/ml and 64µg/ml respectively. The entire investigation of anti-mycobacterial study was conducted against Mycobacterium smegmatis whichis a model organism for mycobacterial studies. These results show that both plants contain potent anti-mycobacterial compound(s) that can be further investigated for purification and isolation of bioactive compound which can be useful in the production of novel drugs.